Sustainability literacy in Indonesian higher education: An interrelationship hierarchical model - Ardaniah, Viqi; Billah, Zakiyah Dania; Rahmantyo, Lastiko Endi; Wisnujati, Andika; Ardhianto, Peter (Philippine Management Review, 2025)
Sustainability literacy motivates higher education institutions to perform sustainable practices; however, improving sustainability literacy through the resilience of the education system and adaptive learning technology has not been sufficiently addressed in previous studies. This study aims to identify the attributes of sustainability literacy in Indonesian higher education. This study offers a valid set of seven aspects and twenty-two criteria implementing a bibliometric analysis and the fuzzy Delphi method. A fuzzy decision-making trial and evaluation (FDEMATEL) is employed to analyze the validated attributes and to determine interrelationships among the attributes. This procedure allows qualitative information to be converted into numerical data and a diagram indicating the attribute interrelationship. The results of this study revealed that adaptive learning technology, resilience of the education system, sustainability-focused courses, and sustainability innovation are the causal attributes of sustainability literacy. Financial literacy, sustainability consciousness, and global citizenship curriculum are the affected attributes of sustainability literacy. Some vital criteria for improving sustainability literacy in HEs include educational innovation, educational technology, and resilience in HE. Hence, this study provides theoretical and managerial contributions based on the proposed attributes.